CCTV surveillance for crime prevention - Piza, Eric L. (Criminology & public policy, 2019)
We report on the findings of an updated systematic review and meta‐analysis of the effects of closed‐circuit television (CCTV) surveillance cameras on crime. The findings show that CCTV is associated with a significant and modest decrease in crime. The largest and most consistent effects of CCTV were observed in car parks. The results of the analysis also demonstrated evidence of significant crime reductions within other settings, particularly residential areas. CCTV schemes incorporating active monitoring generated larger effect sizes than did passive systems. Schemes deploying multiple interventions alongside CCTV generated larger effect sizes than did schemes deploying single or no other interventions alongside CCTV.